Flow Diversion for Intracranial Aneurysms Beyond the Circle of Willis - Yu, Jinlu; Lv, Xianli (Frontiers in Neurology, 2021)
Background: Few reports have shown the endovascular treatment (EVT) outcomes of flow diversion (FD) for intracranial aneurysms beyond the circle of Willis, and the efficacy of this technique remains unclear. Materials and methods: A retrospective study was performed on 22 consecutive patients who were admitted to our hospital, diagnosed with intracranial aneurysms beyond the circle of Willis, and treated with a pipeline embolization device (PED) (Medtronic, Irvine, California, USA) between January 2015 and December 2019. Result: The twenty-two patients were between 16 and 66 years old (mean 44.5 ± 12.7 years), and six patients were male (27.3%, 6/22). Twenty-two patients had 23 aneurysms, of which 2 aneurysms were tandem. The 23 aneurysms were 3-25 mm in diameter (12.2±7.1 mm on average). PED deployment was technically successful in all cases. Two overlapping PEDs were used to cover the aneurysm neck in 3 cases. One PED was used to overlap the two tandem P1 and P2 aneurysms. Other cases were treated with single PEDs. Coil assistance was used to treat seven aneurysms, including 4 recurrent aneurysms and 3 new cases requiring coiling assistance during PED deployment. There were no cases of complications during EVT. All patients were available at the follow-up (mean 10.9 ± 11.4 years). All patients presented with a modified Rankin Score (mRS) of 0. During angiographic follow-up, complete embolization was observed in 22 aneurysms in 21 patients, and one patient had subtotal embolization with the prolongation of stasis in the arterial phase. Conclusion: EVT of intracranial aneurysms beyond the circle of Willis with FD is feasible and effective, with high rates of aneurysm occlusion.